ANALISIS SWOT TINGKAT PENJUALAN PRODUK HERBAL GREEN WORLD STUDI KASUS : STOCKIST HERBAL 1001 DI AMARAPURA SERPONG - Widiati; Agus Wiranto (Journal of Research and Publication Innovation, 2024)
The results of the SWOT analysis show an increase in sales of herbal products at Herbal Stockist 1001 over the last five years. This indicates that Stockist Herbal 1001 remains the main choice for consumers, driven by the superior quality of herbal products and affordable prices. This research also identifies four alternative strategies that can be applied to develop sales of herbal products at Herbal Stockist 1001.First, the (SO) strategy will focus on products with high market share that have received a positive response in the market. Herbal products will become the main selling products at stockists, capitalizing on existing market share and gaining market attention quickly.Second, the (WO) strategy involves promoting limited supplies of key products, informing consumers that the quantity of key sales products is limited for a certain period. Consumers can take advantage of low prices or discounts from distributors when supplies are limited.Third, strategy (ST) will focus on introducing superior products to customers with attention to detail, affordable prices, and easy-to-understand communication.Finally, the (WT) strategy involves entering the market with a brand already known to consumers and developing human resources, especially technicians with expertise in health administration and inspection.By implementing this strategy, Herbal Stockist 1001 can continue to increase sales of herbal products and maintain its position in the competitive market.